2012
DOI: 10.1002/bit.24614
|View full text |Cite|
|
Sign up to set email alerts
|

A pore‐hindered diffusion and reaction model can help explain the importance of pore size distribution in enzymatic hydrolysis of biomass

Abstract: Until now, most efforts to improve monosaccharide production from biomass through pretreatment and enzymatic hydrolysis have used empirical optimization rather than employing a rational design process guided by a theory-based modeling framework. For such an approach to be successful a modeling framework that captures the key mechanisms governing the relationship between pretreatment and enzymatic hydrolysis must be developed. In this study, we propose a pore-hindered diffusion and kinetic model for enzymatic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 37 publications
3
70
0
1
Order By: Relevance
“…The presence of pores and their sizes in fiber walls are critical factors that can affect the hemicelluloses diffusion process (thus, hemicelluloses removal). Previous work showed that the fibers structure and morphology can strongly affect: (1) the removal of non-cellulosic constituents from pulp fibers, such as lignin (Kerr and Goring, 1975); (2) the accessibility of cellulose to chemicals, such as carbon disulfide Miao et al, 2015) during the cellulose xanthation process, or enzymes (Luterbacher et al, 2013) during cellulose enzymatic degradation.…”
Section: Proposed Concept Of Combined Mechanical Refining and Cce Formentioning
confidence: 99%
“…The presence of pores and their sizes in fiber walls are critical factors that can affect the hemicelluloses diffusion process (thus, hemicelluloses removal). Previous work showed that the fibers structure and morphology can strongly affect: (1) the removal of non-cellulosic constituents from pulp fibers, such as lignin (Kerr and Goring, 1975); (2) the accessibility of cellulose to chemicals, such as carbon disulfide Miao et al, 2015) during the cellulose xanthation process, or enzymes (Luterbacher et al, 2013) during cellulose enzymatic degradation.…”
Section: Proposed Concept Of Combined Mechanical Refining and Cce Formentioning
confidence: 99%
“…To minimize the computational intensity, the substrate‐centric kinetic models may collapse elementary enzyme‐substrate interaction steps into coarser steps. For example, Luterbacher et al (, ) described complexation and hydrolysis rates by a lumped rate constant while Hosseini and Shah (2011) and Huron et al () assumed that adsorption reached rapid equilibrium and that all adsorbed cellulases were active. Some models focused only on the changing substrate without explicitly modeling enzyme interaction steps, thus implicitly attributing reaction bottlenecks to substrate properties (Lebaz et al, ; Seo et al, ).…”
Section: Mechanistic Models Of Cellulose Hydrolysis By Cellulasesmentioning
confidence: 99%
“…36 Moreover, some volumes of nanopores between 50 and 100 nm were also observed on the distribution curves of all the pretreated samples, while no pores with a diameter lower than 100 nm were found for the untreated sample. 40 Chundawat et al reported that nanoporous tunnel-like networks as visualized by 3D-electron tomography can be formed within the cell wall after ammonia fiber expansion, and the shape, size (10 to 1000 nm), and spatial distribution of pores depended on their location within the cell wall and the pretreatment conditions. Indeed, 160°C DA pretreatment significantly increases the pore volume between 10 and 1000 nm, primarily due to its near complete removal of hemicellulose and redistribution of lignin.…”
mentioning
confidence: 99%